Prevalence and susceptibility profiles of group a streptococcus in primary care patients with a sore throat and fever in Thailand and the utility of C-Reactive protein and clinical scores for its identification - Greer, R; Althaus, T; Ling, C; Intralawan, D; Nedsuwan, S; Thaipadungpanit, J; Wangrangsimakul, T; Butler, C; Day, N; Lubell, Y (American Society of Tropical Medicine and Hygiene, 2019)
Pharyngitis is usually caused by a viral infection for which antibiotics are often unnecessarily prescribed, adding to the burden of antimicrobial resistance. Identifying who needs antibiotics is challenging; microbiological confirmation and clinical scores are used but have limitations. In a cross-sectional study nested within a randomized controlled trial, we estimated the prevalence and antibiotic susceptibility profiles of group A Streptococcus (GAS) in patients presenting to primary care with a sore throat and fever in northern Thailand. We then evaluated the use of C-reactive protein (CRP) and clinical scores (Centor and FeverPAIN) to identify the presence of GAS. One hundred sixty-nine patients were enrolled, of whom 35 (20.7%) had β-hemolytic Streptococci (BHS) isolated from throat swab culture, and 11 (6.5%) had GAS. All GAS isolates were sensitive to penicillin G. The median CRP of those without BHS isolation was 10 mg/L (interquartile range [IQR] £ 8–18), compared with 18 mg/L (IQR 9–71, P = 0.0302) for those with GAS and 14 mg/L (IQR £ 8–38, P = 0.0516) for those with any BHS isolated. However, there were no significant relationships between CRP > 8 mg/L (P = 0.112), Centor ³ 3 (P = 0.212), and FeverPAIN ³ 4 (P = 1.000), and the diagnosis of GAS compared with no BHS isolation. Identifying who requires antibiotics for pharyngitis remains challenging and necessitates further larger studies. C-reactive protein testing alone, although imperfect, can reduce prescribing compared with routine care. Targeted CRP testing through clinical scoring may be the most cost-effective approach to ruling out GAS infection.